Age and parous-experience dependent changes in emotional contagion for positive infant sounds - Mizuguchi, Nobuaki; Kato, Kenji; Sugawara, Sho K.; Yoshimi, Tatsuya; Goto, Yuta; Takasu, Kaori; Isaka, Tadao (Frontiers in Psychology, 2024)
Introduction Emotional contagion is achieved by inferring and emotionally resonating with other persons’ feelings. It is unclear whether age-related changes in emotional contagion for infant sounds are modulated by the experience of childbirth or childcare. This study aims to evaluate changes in inference and emotional resonance for positive and negative infant sounds (laughter and crying) among women, based on age and parous experience. Methods A total of 241 women (60 young nulliparous, 60 young parous, 60 old nulliparous, and 61 old parous) completed a web-based questionnaire. After listening to three types of infant sounds (laughter, cooing, and crying), participants responded with their valence for hearing infant sounds and estimated infant valence on an 11-point Likert scale. Results The analysis for emotional resonance revealed that the correlation coefficient between self and estimated infant valences was greater in young parous and old nulliparous women than in young nulliparous women, in laughter and cooing sounds. However, correlation coefficients for crying did not differ among any of the four groups. Conclusion The degree of emotional resonance for infant valence increased depending on age and parous-experience for positive infant sounds.